Risk Decision-Making Technology in Gas Reservoir Development at Sichuan Basin. (20th November 2021) - Yu, Guo; Li, Haitao; Chen, Yanru; Liu, Linqing; Zhang, Dongming
Abstract : During the development of complex gas reservoirs, the risk decision-making problem often emerges. Thus, the study on risk assessment is an important tool used to identify potential hazards and create appropriate avoidance measures accordingly. Based on the analysis of seven types of risk factors in gas reservoir development planning, this paper aims to clarify the logical relationship between the risk factors in the strategic planning of natural gas development. The comprehensive research on target risks in the gas reservoir development planning based on stochastic simulation was carried out. The "probability curve scanning method" was used to evaluate objective risk factors, while the decision-making risk factors were evaluated using the "probability curve displacement method." According to the realization probability and dispersion degree of the planned target combined with the risk grade evaluation matrix, the planning target evaluation risk grade was implemented. Moreover, the planning unit risk grade evaluation was obtained at different stages. Regarding the specific production capacity conditions in gas wells (horizontal and vertical wells) and gas reservoir water invasion, the probability method with Monte Carlo stochastic simulation was used to calculate the production and water invasion volumes. The established decision-making risk technology for gas reservoir development, along with the associated supporting procedures, can be used to evaluate the risks of reservoir development planning, production, and water invasion.